Unaware consumers and disclosure of deficiencies - Sefanie Y. Schmitt; Dominik Bruckner (Bamberg University, Bamberg Economic Research Group (BERG), 2022)
We analyze firms' incentives to disclose deficiencies of their goods when consumers lack information. We distinguish two types of information: First, only some consumers are aware of the existence of deficiencies, which reduce the quality of the goods. Second, only some consumers have the expertise to infer the true levels of deficiencies once they are aware of the existence of deficiencies. We show that the interplay of awareness and expertise in a market affects firms' incentives to disclose. In particular, we demonstrate that more awareness and/or expertise in a market does not universally lead to more disclosure but depends on the level of competition in the market. Conversely, increasing competition does not always increase firms' incentives to disclose.
Keywords: D83; L15; 330; Awareness; Competition; Disclosure; Expertise; Product Quality